Hang him twice [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Trail west (Series), 2018)
"When Dooley Monahan saves Buffalo Bill Cody's life, Cody grubstakes him to purchase of a silver mine in the lawless, violent boomtown of Leadville, Colorado. When he guns down three outlaws, the grateful townsfolk make Dooley sheriff. Then he discovers a town tradition: if a sheriff's no good, they hang him. And fingers are starting to point"--